Role of Ultrasound to Monitor Patients With Carpal Tunnel Syndrome Treated With a Local Corticosteroid. (17th January 2019) - Chakkalakkoombil, Sunitha Vellathussery; Nair, Pradeep Pankajakshan; Govindarajalou, Ramkumar; Barathi, Deepak; Marusani, Revanth; Kumar Kottyen Thazhath, Harichandra
Abstract : Objectives: Carpal tunnel syndrome (CTS) is an entrapment neuropathy resulting from compression of the median nerve at the carpal tunnel (CT). We assessed the role of high‐resolution ultrasound (US) in monitoring patients with CTS treated with corticosteroid injection. Methods: We performed high‐resolution US evaluations of the wrists of patients with CTS before and after treatment with local corticosteroid. Thirty‐nine and 17 wrists were included for analysis at the end of 1 and 3 months, respectively. The cross‐sectional area (CSA) and anteroposterior diameter (APD) of the median nerve at the CT and clinical and electrophysiologic data were recorded. We assessed whether changes in US measurements before and after the treatment correlated with clinical and electrophysiologic parameters. Results: The Boston symptom severity scale ( p  < .01), Boston functional status scale ( p  < .01), median nerve motor latency ( p  = .017), median nerve sensory velocity ( p  = .003), and difference in motor latencies ( p  = 0.03) and difference in sensory latencies ( p  = .03) between median and ulnar nerves showed significant changes over 1 or/and 3 months compared to baseline values. Changes in the CSA and APD correlated with changes in some clinical and electrophysiologic parameters. However, measurements of the CSA and APD at 1 or 3 months were not significantly different from baseline values. Conclusions: High‐resolution US parameters such as the APD and CSA of the median nerve at the CT inlet were not useful to monitor patients with CTS treated with corticosteroid injections.